2009
DOI: 10.1111/j.1540-8183.2009.00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Stent Deformation and Gap Formation after Complex Stenting of Left Main Coronary Artery Bifurcations Using Microfocus Computed Tomography

Abstract: MFCT analysis in the 3D phantom model is useful to assess the structural deformation of the stents and gap on vessel wall coverage after complex stenting at the LM bifurcation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…These differences explain why main branchrelated clinical events are more frequent and more severe than side branch-related events and why the previous studies failed to prove the benefit of routine stenting for side branches in bifurcation lesions. Revascularization for clinically insignificant side branches cannot be translated into clinical benefit and may even be harmful (21)(22)(23). In this regard, future studies designed to show the clinical benefit of a new device or treatment strategy in bifurcation lesions should include only the clinically relevant side branches.…”
Section: Discussionmentioning
confidence: 95%
“…These differences explain why main branchrelated clinical events are more frequent and more severe than side branch-related events and why the previous studies failed to prove the benefit of routine stenting for side branches in bifurcation lesions. Revascularization for clinically insignificant side branches cannot be translated into clinical benefit and may even be harmful (21)(22)(23). In this regard, future studies designed to show the clinical benefit of a new device or treatment strategy in bifurcation lesions should include only the clinically relevant side branches.…”
Section: Discussionmentioning
confidence: 95%
“…6 In addition, inadequate side-branch dilatation may result in stent deformation or incomplete stent apposition. 7 In contrast, quantitative coronary angiography (QCA) conducted in the Nordic-Baltic Bifurcation Study III showed better expansion of the side-branch orifice in the FKI group. 6 Because delayed arterial healing characterized by exposed stent struts is considered a possible risk factor for stent thrombosis, 8 struts floating at the side-branch orifice (jailing strut) could affect thrombus formation after DES implantation.…”
mentioning
confidence: 99%
“…Indeed, bench tests have shown that when stents are crushed, there is a trough between the MV and SB stents on the side opposite to the crushed portion (42)(43)(44)(45). If a wire recrosses the MV stent through a distal strut, it may pass outside the stents through the trough before entering the SB stent.…”
Section: Gaining Insight Into Kbmentioning
confidence: 97%